2021
DOI: 10.3390/biom11081184
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Gellan Gum/Silk Fibroin/Chondroitin Sulfate Ternary Injectable Hydrogel for Cartilage Tissue Engineering

Abstract: Hydrogel is in the spotlight as a useful biomaterial in the field of drug delivery and tissue engineering due to its similar biological properties to a native extracellular matrix (ECM). Herein, we proposed a ternary hydrogel of gellan gum (GG), silk fibroin (SF), and chondroitin sulfate (CS) as a biomaterial for cartilage tissue engineering. The hydrogels were fabricated with a facile combination of the physical and chemical crosslinking method. The purpose of this study was to find the proper content of SF a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 67 publications
1
27
0
Order By: Relevance
“…On the other hand, the morphology of the C28/I2 cells was analyzed after being seeded on the surface of the hydrogels for 72 h. Cell shape plays an important role in the phenotypic expression of chondrocytes. The rounded morphology indicates characteristics of the chondrogenic phenotype [ 57 , 58 ]. Figure 3 B shows the SEM micrographs of the cells seeded in the materials, (a) CS1-PF25 and (b) CS1-PF25-TPP.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the morphology of the C28/I2 cells was analyzed after being seeded on the surface of the hydrogels for 72 h. Cell shape plays an important role in the phenotypic expression of chondrocytes. The rounded morphology indicates characteristics of the chondrogenic phenotype [ 57 , 58 ]. Figure 3 B shows the SEM micrographs of the cells seeded in the materials, (a) CS1-PF25 and (b) CS1-PF25-TPP.…”
Section: Resultsmentioning
confidence: 99%
“…However, no distinct peak change were observed between the FTIR spectra of the SA, CCS/SA (1/3), CCS/SA (2/3), BCS/SA (1/3), and BCS/SA (2/3) hydrogels in this study. This demonstrated that the cross-linking reaction between CS and SA was a physical process, and no chemical cross-linking occurred between the polymers [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Naturally derived polymers are widely used in injectable hydrogels for repairing cartilage defects due to their excellent biodegradability, biocompatibility, and similar 3D microenvironment in vivo . However, rapid degradation, poor mechanical properties, and enhanced microenvironment for cell proliferation and differentiation are challenges in practical applications ( Jian et al, 2012 ; Lee et al, 2021 ). The combination of natural and synthetic polymers can play to their respective strengths and compensate for their weaknesses ( Peng et al, 2019 ; Li et al, 2021c ).…”
Section: Materials Of Injectable Hydrogelsmentioning
confidence: 99%